Models of Community Development Practice - Allen B. Moore; Lilian H. Hill (Adult Education Research Conference, 2000)
We address two models developed in a research project that explored community development practice. We begin with a brief introduction of our research, continue with the presentation of the models, relate them to existing theory, and conclude with why the introduction of new models is justified.